Multiple pulmonary cavernous haemangiomas with concurrent primary pulmonary adenocarcinoma: a case report and literature review - Wang, Xiao; Ren, Tao; You, Hui; Han, Wenya; Guo, Jialong; Wang, Meifang (Frontiers in Oncology, 2024)
Background: Cavernous haemangiomas (CHs) commonly occurred in the skin, subcutaneous tissue, muscles, and liver. Pulmonary cavernous haemangiomas (PCHs) are quite rare and usually present with nonspecific clinical symptoms. When lung cancer patients are complicated with pulmonary cavernous hemangiomas, radiologically, these hemangioma lesions can be easily misinterpreted as intrapulmonary metastases, potentially resulting in misdiagnosis, or missed diagnosis. Case presentation: The present study reported the case of a 53‑year‑old female patient with pulmonary adenocarcinoma coexisting with multiple PCHs. 18F‑FDG-Positron emission tomography-computed tomography (PET-CT) showed an elevated glucose metabolism in the apicoposterior segment of the left upper lobe; however, the other nodules were not hypermetabolic. Percutaneous lung biopsy was performed on the nodule in the apicoposterior segment of the left upper lobe, which were diagnosed as primary adenocarcinoma. Some nodules in the upper left lobe underwent wedge resection by video-assisted thoracic surgery (VATS) and intraoperative frozen section identified as PCHs. Finally, the patient underwent lobectomy of the left upper lobe via VATS, cancerous nodule in the apicoposterior segment of the left upper lobe underwent genetic molecular testing of PCR‑Sanger sequencing, suggested EGFR mutation, and patient received treatment with Osimertinib. During the 4‑months follow‑up, contrast‑enhanced CT showed no recurrence of either disease. PCHs are rare benign tumours of the lung, which can lead to misdiagnosis due to their non-specific clinical symptoms and radiological features, especially when they coexist with lung cancer. PCHs is easily misunderstood as metastatic lung cancer, in this case, PET-CT can assist in differentiating benign from malignant. For the cases of early lung cancer complicated with PCHs, lung cancer can be surgically resected, and whether PCHs should be removed or not should be determined according to the size and distribution of the lesions.